2001
DOI: 10.1029/2000jb900463
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters and three‐dimensional attenuation structure from the inversion of microearthquake pulse width data: Method and synthetic tests

Abstract: Abstract. We propose a new method to determine source parameters and attenuation structure of a three-dimensional medium based on first P rise time and total pulse width measurements from microearthquake data. The effects of fault finiteness on seismic radiation are taken into account by assuming the rupture model for a circular crack of Sato and Hirasawa (1973). Ray theory synthetic seismograms in a constant Q anelastic medium are computed to derive a set of nonlinear equations which relate the source and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 42 publications
(30 reference statements)
1
32
0
1
Order By: Relevance
“…This phenomenon, known as the directivity source effect, has been theoretically explained in terms of both the spatial finiteness of the seismic source and its finite rupture velocity (e.g. Zollo & de Lorenzo 2001): It has been demonstrated (Boatwright 1984) that the directivity source effect depend also on the shape of the fractured area (unilateral, circular or mixed).…”
Section: Theoretical Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon, known as the directivity source effect, has been theoretically explained in terms of both the spatial finiteness of the seismic source and its finite rupture velocity (e.g. Zollo & de Lorenzo 2001): It has been demonstrated (Boatwright 1984) that the directivity source effect depend also on the shape of the fractured area (unilateral, circular or mixed).…”
Section: Theoretical Relationshipsmentioning
confidence: 99%
“…We propose an improvement of the inversion method of Zollo & de Lorenzo (2001) to account for a priori information on dip and strike. With respect to the previous study, the imposition of (δ, φ) allows us to reduce the number of unknown model parameters from four (L, δ, φ and Q p ) to only two (L and Q p ).…”
Section: Inversion Techniquementioning
confidence: 99%
“…Pencitraan dari Qfactor dapat digunakan untuk menentukan lokasi dan extension of magma bodies pada daerah vulkanik dan detail kontribusi fluida pada daerah patahan maupun berdasarkan pada tingginya porositas efektifnya [4,5]. Selain itu sebenarnya nilai Q-factor juga dapat digunakan sebagai indikator adanya hidrokarbon dan panas bumi [6,7].…”
Section: Gambar 1 Peta Dan Posisi Stasiun Seismik Gunung Semeruunclassified
“…Obviously, the most limiting assumption of this method is that it neglects the directivity effect of the seismic radiation generated by a finite dimensional seismic source (Zollo and De Lorenzo 2001; Tselentis et al 2009). The directionality of the source will have a limited effect as long as it only affects the amplitude of the signal and not the spectral content.…”
Section: Rise Time As a Measure Of Qmentioning
confidence: 99%
“…Several investigations in geothermal areas (Zucca, Hutchings and Kasameyer 1994; Sanders and Nixon 1995; Sanders et al 1995; Wu and Lees 1996; Zollo and De Lorenzo 2001) have shown that the imaging of the quality factor Q is a useful tool to define location and extension of magma bodies in volcanic areas and to detail the fluid contribution through fracture systems. Usually, a high degree of cracking or high effective porosity (Zucca et al 1994; Sanders et al 1995) and the presence of water/gas in the fractures lower Q p values.…”
Section: Introductionmentioning
confidence: 99%